The World Order Crisis and the Threats for Russia and the World - D. B. Ryurikov (Vestnik MGIMO-Universiteta)
Crises in global finance and economy, the threat of wars and tension in world relations, the degradation of the non-material bases of civilization, i.e. morality, law, politics, and culture, do not bother a group of influential financial and political figures of the West : they believe that after a sequence of crises and wars, a "new world order", the NWO, will be established. Projected globally once by the "hard", once by the "soft" power, the ideology and practice of the NWO negates the foundations of civilization gained by ordeals and sufferings of mankind, and means the departure from the principles and norms of the actual world order valid until the end of the 20th century. Essentially, the NWO is an anticivilizacion. If the project is allowed to be implemented, the lives of humans will change beyond recognition. Thus, the key challenge of our time : do not let the project to be realized, consolidate the forces opposing the NWO.